EVALUATING THE QUALITY OF THE FINAL THESIS PREPARATION PROCESS: A COMBINATION OF SERVQUAL AND IMPORTANCE-PERFORMANCE ANALYSIS - Šileikienė, Irma; Usovaitė, Ana (PROFESSIONAL STUDIES: Theory And Practice, 2022)
The aim of this article is to present the analysis of of the final thesis preparation process by appling a combination of SERVQUAL and importance-performance analysis. The scores of the parameters of tangibility, accountability, reliability, reliability, assurance and empathy were calculated. The results showed that among the students’ expectations and perceptions, empathy has the highest gap across all the metrics and reliability has the lowest gap. Similar results were obtained in both academic years. The importance-performance analysis (IPA) method was used to present and analyse the results obtained. The attributes that need urgent attention as they may lead to customer dissatisfaction were identified.These are that lecturers should treat students equally and with respect and that the faculty should take student feedback into account in improving the processes of preparing and defending theses